Exploitation of the invasive Asian Hornet Vespa velutina by the European Honey Buzzard Pernis apivorus. Issue 3 (3rd July 2019) - Macià, F. X.; Menchetti, M.; Corbella, C.; Grajera, J.; Vila, R.
ABSTRACT: This paper reports the first case of predation on the nests of Asian Hornet Vespa velutina by the European Honey Buzzard Pernis apivorus, as well as the use of this resource by a breeding pair to provision their nestlings. The Asian Hornet is listed among the 100 most invasive alien species and is expanding in Western Europe. Our finding opens the door to a number of questions, including the effects of this additional allochthonous resource on the European Honey Buzzard populations, as well as the potential of this raptor as a biocontrol agent.